Penerapan teknologi papan panel di Desa Parigi Kecamatan Tinggimoncong Kabupaten Gowa - Syamsuddin Mustafa; Hamsina Hamsina (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
UMKM Sentosa in Parigi Village is engaged in the business of making furniture or household furniture made from pine wood is partner by KKN PPM activity. This UMKM was established in 2013 with 15 employees. The problem by UMKM is the large amout of pine wood sawdust produced in the process of making furniture . This on time production to produce 570 kg of pine wood sawdust. This certainly has an impact on the surrounding environment because this waste accumulate in partner UMKM without processing furthermore. Furthermore Whereas pine wood waste can be processed into panel board products by adding coconut fiber and mushroom waste as an adhesive. Waste mushroom is a by product of processing mushrooms where the mushrooms with quality that do not meet export standards are piled up and become waste that disturbs the environment. Therefore the KKN PPM activity aims to provide the introduction and diffusion of pine wood powder processing, coconut fiber and straw mushroom waste into panel boards that can overcone the problems faced by UMKM .  The method used to achieve the above objectives is to carry out intensive assistance by the KKN PPM implementation team and student to the furniture UMKM group community both in the production   process to marketing . The production process begins with providing an understanding of the processing of pine wood sawdust waste into panel boards and processing of natural resources in the form of plants into cattle herbs in increasing the vitality and productivity of cattle. Variuos supporting activities have also been implemented such as coaching the younger generation through sports and arts activities as weel as social activities. The results of the KKN PPM activities show that the production of panel boards produced after the program 50 pieces / month for one group consisting of 5 family members where for 1 panel board can be sold for Rp. 15.000. Whereas livestoct herbal medicine is sold for RP.50.000/ 1000 ml.